Penataan jalur pejalan kaki untuk mendukung Green Campus di kampus Universitas Diponegoro Tembalang - Nararya Adi Prasetya; P. Purwanto; Maryono Maryono (Pelantar Press, 2021)
One approach to realizing a green campus is by providing a comfortable space for non-motorized transportation. Walking is the cheapest, low-emission non-motorized transportation, so accessibility to pedestrians should be prioritized. Providing more space for pedestrians which will change the orientation of road infrastructure that has been more pro-motorized. Diponegoro University, which is the green campus pilot project of the Ministry of Research, Technology and Higher Education, has complete pedestrian paths. However, the current condition is still not appropriately utilised because the movement of academicians is still using motorized vehicles. To preserving the orientation of the existing green campus, it is necessary to evaluate the pedestrian path that is suitable by regulation physically. The results of research on pedestrian paths at the Undip Tembalang Campus indicate that it is required to repair and change the road design that is related to the comfort of people walking, and affects how pedestrian paths are used. Official regulations and policies from the campus will also have an impact on motorized vehicle use. Changes to empower those in the campus environment and energy-efficient actions are carried out by improving the accessibility of campus residents to use public transportation and non-motorized transportation to campus.